2023
DOI: 10.1097/ju.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

National Adherence to Guidelines for Antimicrobial Prophylaxis for Patients Undergoing Radical Cystectomy

Abstract: Purpose: The sentinel reference for antibiotic prophylaxis for radical cystectomy with ileal conduit in the AUA Guidelines reports data from 2003-2013 and has not been updated in the interim. Here, we assess adherence to antibiotic prophylaxis guidelines among patients undergoing radical cystectomy with ileal conduit for bladder cancer using a large national database. As a secondary objective, we assess the association between antimicrobial use and postoperative infection during the index admission following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Prunty et al [40 ▪▪ ] showed that 73% of patients fail to receive guideline-based antibiotic prophylaxis when undergoing radical cystectomy with conduit, which was largely driven by extended duration antibiotic use. Among 6708 patients undergoing cystectomy with ileal conduit, only 28% were given prophylaxis according to AUA guidelines.…”
Section: Compliancementioning
confidence: 99%
“…Prunty et al [40 ▪▪ ] showed that 73% of patients fail to receive guideline-based antibiotic prophylaxis when undergoing radical cystectomy with conduit, which was largely driven by extended duration antibiotic use. Among 6708 patients undergoing cystectomy with ileal conduit, only 28% were given prophylaxis according to AUA guidelines.…”
Section: Compliancementioning
confidence: 99%
“…To the Editor: Prunty et al present data on the low adherence to antimicrobial prophylaxis guidelines in patients undergoing radical cystectomy and ileal conduit. 1 More specifically, they queried the Premier Healthcare Database and found that only 28% of patients between January 2015 and March 2020 received guideline-concordant prophylaxis. Furthermore, they found an association of increased antibiotic usage with a greater risk of any infectious event, including urinary tract infection, pyelonephritis, bacteremia, and pneumonia.…”
mentioning
confidence: 99%
“…Prunty et al stratified guideline discordance by failed adherence to antibiotic duration and/or selection; they found that 37% of the cases of nonadherence were due to prolonged duration, defined as antibiotics extending into postoperative day 2. 1 This duration, however, corresponds to the 2008 American Urological Association best practice statement. 2 More recently, published in 2019, the guidelines were updated to recommend a single perioperative dose of antibiotics for radical cystectomy and ileal conduit.…”
mentioning
confidence: 99%
“…Prunty et al recently reported that among almost 7,000 patients from a large insurance claims database undergoing radical cystectomy over a 5-year period, only 28% were given perioperative prophylaxis considered adherent to the AUA best practice guideline on antimicrobial prophylaxis. 4 The most common disqualifier from guideline adherence was prolonged periprocedural antibiotic use, defined as prophylaxis longer than 24 hours, which was seen in 37% of patients. Patients with guideline-discordant regimens were more likely to suffer from postoperative infections including pyelonephritis and pneumonia.…”
mentioning
confidence: 99%